Modified adsorption material for water pollution and preparation method thereof
By linking polyether sulfone with sodium thiazolebenzenesulfonate, a multifunctional adsorption material was prepared, which solved the problem of heavy metal ion pollution and degradation of modified membrane performance in existing water treatment technology, and achieved improved anti-pollution performance and adsorption Performance improvement.
Patent Information
- Application Number
- CN202411702197.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-13
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water treatment technology cannot effectively remove heavy metal ion pollution, and the performance of modified membrane materials decreases during use, the types of adsorption are limited, and the scope of use needs to be expanded.
Using polyether sulfone as the matrix material, by introducing chloromethyl active groups and bonding with sodium thiazole benzenesulfonate, a modified adsorbent material containing multifunctional adsorption is prepared, using its hydrophilicity and unbonded The electrons form a stable structure and perform metal ion adsorption.
The anti-pollution performance of the modified film and the adsorption performance of the heavy metal ions are improved, the total pollution index is reduced, the water flux recovery rate is increased, and the application range of adsorbent materials is expanded.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water pollution control, in particular to a modified adsorption material for water pollution and a preparation method thereof. Background Art
[0002] With the development of the global economy, a large amount of industrial wastewater and waste gas emissions are directly discharged without treatment and cannot be recycled, resulting in serious excessive levels of heavy metal ions in water bodies. The status quo of water pollution is becoming increasingly serious. Heavy metal pollution in the water environment will not only cause significant economic losses, but also threaten the health of various life forms including humans. The current sewage treatment situation is not optimistic. Sewage treatment generally involves adding reducing agents such as iron powder to the wastewater to reduce the heavy metal ions and remove those metal ions present in the wastewater, but it is easy to cause secondary pollution. Existing water treatment technology cannot meet people's increasingly high water quality requirements. Therefore, the treatment of heavy metal wastewater has become one of the research hotspots at home and abroad.
[0003] The adsorption method has attracted the attention of scholars at home and abroad because of its wide material source, low cost and the advantage of avoiding re-pollution; the invention patent CN108404686 discloses a preparation method of a metal ion adsorption sewage separation membrane, wherein graphene oxide is modified by polyphenol compounds such as tannin, and then blended with PVDF powder to obtain a metal ion adsorption sewage separation membrane, and a large number of oxygen-containing polar groups such as carboxyl, phenolic hydroxyl, epoxy and the like contained in the membrane are utilized to efficiently adsorb and desorb low-concentration metal ions, and the membrane can be used repeatedly, but the modified membrane material obtained by blending in the prior art will have the modifier precipitated from the modified membrane material after a period of use, resulting in a decrease in the performance of the membrane material, and the types of heavy metal ions adsorbed by the separation membrane are limited, and the scope of use needs to be further expanded; the present invention uses polyethersulfone as a matrix material, introduces chloromethyl active groups on its surface, and then bonds with the prepared organic small molecules containing sodium sulfonate and thiazole to obtain a modified adsorption material containing multifunctional adsorption, which has excellent adsorption performance and can be reused. Summary of the invention
[0004] The technical problem solved by the invention is to provide a modified adsorption material for water pollution and a preparation method thereof, thereby solving the problem of serious heavy metal ion pollution in wastewater.
[0005] The technical solution of the present invention is: A method for preparing a modified adsorbent material for water pollution, the preparation method is carried out according to the following steps: (1) Add sodium benzaldehyde-4-sulfonate to an organic solvent, stir evenly, then add 2-aminothiazole, stir to react, and after the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol, and dry to obtain sodium thiazolebenzenesulfonate. The preparation process is as follows:
[0006] (2) Add 100 parts by weight of vacuum-dried polyethersulfone to 98% concentrated sulfuric acid, stir at 20-35°C until completely dissolved, then lower the reaction temperature to -5-5°C, dropwise add 150-250 parts of chloromethyl ether, react for 5-8 hours, add deionized water to precipitate, filter, wash with deionized water and anhydrous ethanol until neutral, and dry to obtain chloromethylated polyethersulfone.
[0007] (3) Add chloromethylated polyethersulfone to N,N-dimethylacetamide, stir to swell, then add sodium thiazole benzene sulfonate, after the reaction is completed, centrifuge for 5-10 minutes, add ethanol to precipitate, filter, wash with ethanol, and dry at 20-35°C to obtain a modified adsorption material for water pollution. The preparation process is as follows:
[0008] Furthermore, the organic solvent in step (1) is ethanol or isopropanol.
[0009] Furthermore, in step (1), the mass of 2-aminothiazole is 160-230% of that of benzaldehyde-4-sulfonic acid.
[0010] Furthermore, in step (1), the reaction temperature is 80-100° C. and the reaction time is 2-5 h.
[0011] Furthermore, in the step (3), the mass fraction of chloromethylated polyethersulfone in N,N-dimethylacetamide is 12-20 g / mL.
[0012] Furthermore, the mass of sodium thiazole benzene sulfonate in step (3) is 260-550% of that of chloromethylated polyether sulfone.
[0013] Furthermore, in step (3), the reaction temperature is 90-110° C. and the reaction time is 8-16 h.
[0014] Furthermore, the centrifugal speed in step (3) is 3000-3500 r / min The beneficial technical effects of the present invention are: Sodium thiazolebenzenesulfonate containing N and S heteroatoms is prepared by the Schiff base reaction of sodium benzaldehyde-4-sulfonate and 2-aminothiazole. Then, chloromethyl active groups are introduced into polyethersulfone under the action of chloromethyl ether to obtain chloromethylated polyethersulfone. Then, the chloromethyl active groups are used to react with the N atoms on the thiazole ring for quaternization to prepare modified adsorption materials for water pollution containing multifunctional groups.
[0015] Zwitterionic polymers are hydrophilic, have strong hydration ability, and have good anti-pollution ability. The surface of the modified membrane contains quaternary ammonium cations and sulfonic acid anions, which can form a hydration layer on the membrane surface, and the modifier will precipitate from the modified membrane material, thereby improving the anti-pollution performance of the modified membrane. In addition, the introduced functional groups contain N and S atoms with unbonded lone pairs of electrons, which can form coordination bonds with metal ions with a pair of lone pairs of electrons to form a stable structure similar to a small molecule chelate, so that specific metal ions can be selectively complexed from an aqueous solution containing metal ions. In addition, polyethersulfone is an ultrafiltration membrane material with stable chemical properties. The microporous structure of the membrane itself has a good barrier effect on large particle pollutants. By hydrophilic modification of its surface and introduction of functionalized adsorption groups, the total pollution index of the prepared membrane adsorption material is reduced and the water flux recovery rate is increased, and the adsorption performance of heavy metal ions is greatly improved. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0017] (1) Add 50 parts by weight of sodium benzaldehyde-4-sulfonate to ethanol, stir evenly, then add 105 parts of 2-aminothiazole, stir and react, react at 95° C. for 4 hours, cool to room temperature, filter, wash with anhydrous ethanol, and dry to obtain sodium thiazolebenzenesulfonate.
[0018] (2) Add 100 parts by weight of vacuum-dried polyethersulfone to 98% concentrated sulfuric acid, stir at 30°C until completely dissolved, then lower the reaction temperature to 0°C, dropwise add 160 parts of chloromethyl ether, react for 7 hours, add deionized water to precipitate, filter, wash with deionized water and anhydrous ethanol until neutral, and dry to obtain chloromethylated polyethersulfone.
[0019] (3) Add 100 parts by weight of chloromethylated polyethersulfone to N,N-dimethylacetamide, stir to swell, then add 260 parts of sodium thiazolebenzenesulfonate, react at 105°C for 12 hours, centrifuge for 5 minutes, add ethanol to precipitate, filter, wash with ethanol, and dry at 25°C to obtain a modified adsorbent material for water pollution. Example 2
[0020] (1) Add 80 parts by weight of sodium benzaldehyde-4-sulfonate to isopropanol and stir evenly, then add 160 parts of 2-aminothiazole and stir to react. After reacting at 90° C. for 5 h, cool to room temperature, filter, wash with anhydrous ethanol, and dry to obtain sodium thiazolebenzenesulfonate.
[0021] (2) Add 100 parts by weight of vacuum-dried polyethersulfone to 98% concentrated sulfuric acid, stir at 20°C until completely dissolved, then lower the reaction temperature to -2°C, dropwise add 225 parts of chloromethyl ether, react for 6 hours, add deionized water to precipitate, filter, wash with deionized water and anhydrous ethanol until neutral, and dry to obtain chloromethylated polyethersulfone.
[0022] (3) Add 100 parts by weight of chloromethylated polyethersulfone to N,N-dimethylacetamide, stir to swell, then add 320 parts of sodium thiazolebenzenesulfonate, react at 100°C for 15 hours, centrifuge for 8 minutes, add ethanol to precipitate, filter, wash with ethanol, and dry at 35°C to obtain a modified adsorption material for water pollution. Example 3
[0023] (1) Add 45 parts by weight of sodium benzaldehyde-4-sulfonate to isopropanol and stir evenly, then add 80 parts of 2-aminothiazole and stir to react. After reacting at 80° C. for 5 h, cool to room temperature, filter, wash with anhydrous ethanol, and dry to obtain sodium thiazolebenzenesulfonate.
[0024] (2) Add 100 parts by weight of vacuum-dried polyethersulfone to 98% concentrated sulfuric acid, stir at 25°C until completely dissolved, then lower the reaction temperature to 3°C, dropwise add 230 parts of chloromethyl ether, react for 8 hours, add deionized water to precipitate, filter, wash with deionized water and anhydrous ethanol until neutral, and dry to obtain chloromethylated polyethersulfone.
[0025] (3) Add 100 parts by weight of chloromethylated polyethersulfone to N,N-dimethylacetamide, stir to swell, then add 400 parts of sodium thiazolebenzenesulfonate, react at 105°C for 13 hours, centrifuge for 9 minutes, add ethanol to precipitate, filter, wash with ethanol, and dry at 30°C to obtain a modified adsorption material for water pollution. Example 4
[0026] (1) Add 150 parts by weight of sodium benzaldehyde-4-sulfonate to ethanol or isopropanol, stir evenly, then add 315 parts of 2-aminothiazole, stir and react, react at 85° C. for 3 h, cool to room temperature, filter, wash with anhydrous ethanol, and dry to obtain sodium thiazolebenzenesulfonate.
[0027] (2) Add 100 parts by weight of vacuum-dried polyethersulfone to 98% concentrated sulfuric acid, stir at 30°C until completely dissolved, then lower the reaction temperature to 1°C, add 190% chloromethyl ether dropwise, react for 6 hours, add deionized water to precipitate, filter, wash with deionized water and anhydrous ethanol until neutral, and dry to obtain chloromethylated polyethersulfone.
[0028] (3) Add 100 parts by weight of chloromethylated polyethersulfone to N,N-dimethylacetamide, stir to swell, then add 480 parts of sodium thiazolebenzenesulfonate, react at 110°C for 12 hours, centrifuge for 6 minutes, add ethanol to precipitate, filter, wash with ethanol, and dry at 35°C to obtain a modified adsorption material for water pollution. Example 5
[0029] (1) Add 20 parts by weight of sodium benzaldehyde-4-sulfonate to ethanol or isopropanol, stir evenly, then add 45 parts of 2-aminothiazole, stir and react, react at 95° C. for 3 h, cool to room temperature, filter, wash with anhydrous ethanol, and dry to obtain sodium thiazolebenzenesulfonate.
[0030] (2) Add 100 parts by weight of vacuum-dried polyethersulfone to 98% concentrated sulfuric acid, stir at 35°C until completely dissolved, then lower the reaction temperature to 0°C, dropwise add 215 parts of chloromethyl ether, react for 7 hours, add deionized water to precipitate, filter, wash with deionized water and anhydrous ethanol until neutral, and dry to obtain chloromethylated polyethersulfone.
[0031] (3) Add 100 parts by weight of chloromethylated polyethersulfone to N,N-dimethylacetamide, stir to swell, then add 550 parts of sodium thiazolebenzenesulfonate, react at 100°C for 15 hours, centrifuge for 10 minutes, add ethanol to precipitate, filter, wash with ethanol, and dry at 30°C to obtain a modified adsorption material for water pollution.
[0032] Comparative Example 1 (1) Add 100 parts by weight of vacuum-dried polyethersulfone to 98% concentrated sulfuric acid, stir at 25°C until completely dissolved, then lower the reaction temperature to 0°C, dropwise add 210 parts of chloromethyl ether, react for 8 hours, add deionized water to precipitate, filter, wash with deionized water and anhydrous ethanol until neutral, and dry to obtain chloromethylated polyethersulfone.
[0033] Anti-pollution performance test: The modified adsorbent material for water pollution prepared in each embodiment and the chloromethylated polyether sulfone prepared in the comparative example were dissolved in N,N-dimethylacetamide, stirred until completely dissolved to obtain a casting liquid, and then the casting liquid was sealed and allowed to stand for degassing for 12 hours; then the casting liquid was evenly cast on a glass plate, placed in an oven at 60°C and dried for 24 hours. After the film was dried, it was peeled off the glass plate to obtain a membrane adsorption material, and performance testing was performed.
[0034] The prepared membrane adsorption material was pre-pressed at 0.15MPa until the water flux was stable, and the pure water and bovine serum albumin (BSA) solution (phosphate buffer, pH=7) were alternately filtered every 20 minutes for a total of 60 minutes. First, the pure water flux test was started, and the pure water flux J0 was recorded every 5 minutes. After running for 20 minutes, the pure water was replaced with 1g / L BSA solution, and the running time was 20 minutes. The permeation flux J of BSA was recorded every 5 minutes. BSA , and calculate the total contamination index R of the membrane adsorption material after BSA solution treatment. The calculation formula is as follows: R(%)=(1-J BSA / J0)×100 Finally, the BSA solution was switched to pure water and the solution was run for 20 min. The recovery flux J of pure water was recorded every 5 min. r Before testing the pure water recovery flux, the membrane adsorption material was immersed in deionized water for 2 h. The water flux recovery rate (FRR) was calculated as follows: FRR(%)=J r / J0×100
[0035] It can be seen from the above table that with the increase of the proportion of sodium thiazole benzene sulfonate and quaternary ammonium salt in the composite membrane material, the total pollution index shows a downward trend. This is because the modified membrane surface introduces a highly hydrophilic sulfonic acid group, and the hydrophilic membrane surface of the modified membrane forms a hydration layer with water molecules, so that the membrane surface is enriched with hydrophilic groups and the adsorption of proteins is reduced. Therefore, membrane pollution can be alleviated to a certain extent. Compared with the comparative example 1 without functional adsorption groups, the total pollution index is reduced by 20%.
[0036] A simple and direct method to characterize the anti-pollution performance of the membrane is the water flux recovery rate. The larger the water flux recovery rate, the better the anti-pollution performance of the membrane. An increase in the flux recovery rate indicates that the irreversible pollution index has greatly decreased. The water flux recovery rate of the modified membrane gradually increases, reaching a maximum of 96%, an increase of 27% compared with Comparative Example 1, indicating that the anti-pollution performance of the modified membrane has been improved.
[0037] Static adsorption capacity test: Weigh a certain mass of membrane adsorption material and place it in different metal ion solutions with a concentration of 500 mg / L. Oscillate at a constant temperature in a constant temperature oscillator for 12 hours. Use an ultraviolet-visible photometer to measure the concentration of metal ions in the solution, and calculate the equilibrium adsorption capacity according to the following formula: Q (mg / g) = (C0-C) × V / M C0: initial concentration of solution (mg / mL); C: concentration of solution after adsorption (mg / mL); V: volume of solution (mL); M: mass of dry film (mg).
[0038]
[0039] It can be seen from the above table that with the increase of sodium thiazole benzene sulfonate and quaternary ammonium salt content on the surface of the modified membrane, the adsorption capacity of metal ions increases. The sodium sulfonate group is hydrophilic and has strong hydration ability. In addition, there are N and S atoms with unbonded lone pairs of electrons in the functional group, which can bind to Cu with a pair of lone pairs of electrons. 2+ The metal ions form coordination bonds to form a stable structure similar to a small molecule chelate, so it can selectively complex specific metal ions from an aqueous solution containing metal ions, thereby enhancing the adsorption performance of the membrane surface; although Comparative Example 1 does not contain zwitterions and N, S heterocycles, the chloromethylated polyether sulfone itself has a microporous structure and has a certain adsorption capacity for metal ions.
[0040] Quaternary ammonium salts have a cationic structure and can effectively treat Cr2O7 in wastewater. 2- With the increase of quaternary ammonium salt content on the surface of the modified membrane, the adsorption of Cr2O7 2- The adsorption amount of quaternary ammonium cations gradually increased, which is because the adsorption of quaternary ammonium cations on Cr2O7 2- The adsorption of anions is achieved through association, mainly chemical adsorption. The reason why the adsorption amount decreases is that the adsorption on the surface of the modified membrane has reached saturation, so the adsorption amount of metal ions is reduced, but the adsorption performance at this time is still superior.
[0041] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. A method for preparing a modified adsorbent material for water pollution, characterized in that: The preparation method is carried out according to the following steps: (1) adding sodium benzaldehyde-4-sulfonate to an organic solvent, stirring evenly, then adding 2-aminothiazole, stirring to react, and after the reaction is completed, cooling to room temperature, filtering, washing with anhydrous ethanol, and drying to obtain sodium thiazolebenzenesulfonate; (2) Add 100 parts by weight of vacuum-dried polyethersulfone to 98% concentrated sulfuric acid, stir at 20-35°C until completely dissolved, then lower the reaction temperature to -5-5°C, dropwise add 150-250 parts of chloromethyl ether, react for 5-8 hours, add deionized water to precipitate, filter, wash with deionized water and anhydrous ethanol until neutral, and dry to obtain chloromethylated polyethersulfone; (3) Add chloromethylated polyethersulfone to N,N-dimethylacetamide, stir to swell, then add sodium thiazolebenzenesulfonate, after the reaction is completed, centrifuge for 5-10 minutes, add ethanol to precipitate, filter, wash with ethanol, and dry at 20-35°C to obtain a modified adsorption material for water pollution; The mass of 2-aminothiazole in step (1) is 160-230% of benzaldehyde-4-sulfonic acid; The mass of sodium thiazole benzene sulfonate in step (3) is 260-550% of that of chloromethylated polyether sulfone.
2. The method for preparing a modified adsorbent material for water pollution according to claim 1, characterized in that: The organic solvent in step (1) is ethanol or isopropanol.
3. The method for preparing a modified adsorbent material for water pollution according to claim 1, characterized in that: In the step (1), the reaction temperature is 80-100° C. and the reaction time is 2-5 h.
4. The method for preparing a modified adsorbent material for water pollution according to claim 1, characterized in that: In the step (3), the mass fraction of chloromethylated polyethersulfone in N,N-dimethylacetamide is 12-20 g / mL.
5. The method for preparing a modified adsorbent material for water pollution according to claim 1, characterized in that: In the step (3), the reaction temperature is 90-110° C. and the reaction time is 8-16 h.
6. The method for preparing a modified adsorbent material for water pollution according to claim 1, characterized in that: The centrifugal speed in step (3) is 3000-3500 r / min.
Citation Information
Patent Citations
N-acetylethylenediamine chelate resin and preparation method thereof
CN101967209A
Homogeneous anion exchange membrane and preparation method thereof
CN102728237A
Method for fast selectively adsorbing mercury ions in water based on thiazole derivative functionalized superfine fibers
CN106268702A
Preparation method of quaternized and sulfonated polyethersulfone ultrafiltration membrane
CN116212640A
Sulfonated polyethersulfone as well as preparation method and application thereof
CN116589681A
